Same-day discharge after early mobilisation and increased frequency of physiotherapy following hip and knee arthroplasty - Retha-Mari Prinsloo; Monique M. Keller (AOSIS, 2022)
Background: Advanced rehabilitation pathway (ARP) after hip and knee arthroplasties is popular globally and is gaining ground in South Africa (SA). A multidisciplinary team in Rustenburg, SA, has implemented an ARP with the first same-day discharge (SDD) from hospital. The lack of evidence of physiotherapy protocols within an ARP determined our study. Objectives: Determine and compare hospital length of stay (LOS) (hours), patient satisfaction (Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC)), patient safety (30-day re-admission) and cost between the two cohorts. Method: A quantitative prospective patient (treatment) group receiving early mobilisation with increased frequency of physiotherapy on post-operative day zero (POD0) was compared to a conservatively managed retrospective historical (control) group following post-operative elective hip and knee arthroplasties. Results: Results for the prospective group which were significantly improved relative to the retrospective group included decreased LOS (median 7.650, p  0.001), less pain at 6 weeks (mean 16.20, standard deviation [SD] = 2.673, p  0.001), less stiffness (mean 5.82, SD = 1.214, p = 0.007), higher function (mean 54.87, SD = 8.544, p  0.001), lower hospital cost (mean R43 340, p  0.001) and physiotherapy cost (mean R1069, p  0.001), and total costs compared to the retrospective group (mean R117 062, p  0.001). Conclusion: Safe and cost-effective SDD is possible in an ARP with earlier mobilisation and increased frequency of physiotherapy on POD0. Clinical implications: Achieving safe SDD after hip and knee arthroplasty surgeries saved costs and improved patient satisfaction, with a decrease in LOS being beneficial for medical funders and stakeholders including government aiming to implement National Health Insurance (NHI) in the future.